ANEURYSMAL BONE CYST (ABC) IN FIFTH METACARPAL RIGHT HAND OF A MALE CHILD WITH HEMOPHILIA TREATED BY STEROID INJECTION: A CASE REPORT - Agus Wahyudi; Mujaddid Idulhaq; Rhyan Darma Saputra; Pamudji Utomo (Universitas Muhamadiyah Surakarta, 2020)
ABSTRACTAneurysma bone cyst (ABC) is a rare case, rapidly growing, and destructive benign bone tumor that rarely involves the bones of the hand. Pathogenesis of these tumors remains controversial and may be vascular, traumatic, or genetic disorders. This study aimed to evaluate patient’s out come after steroid injection. A male child presented with a history of pain and local swelling over his fifth metacarpal right hand of two months duration with hemofilia condition. Physical and radiographic examination of the hand was consistent with aneurysmal bone cyst. The patient the VIII factor 2 hours before doing steroid injection on his lump over fifth metacarpal right hand. A month evaluation after injection for this patient, we had a good result clinically and radiologically. Radiological evaluation obtained appearance of cortex thickening on the bone affected. We concluded that steroid injection should be considered as one of ABC’s treatment with hemophilia, but the outcome still needed more evaluation. Keywords: Aneurysmal Bone Cyst, Hemophilia, Steroid Injection ABSTRAK Kista tulang aneurisma adalah kasus yang jarang terjadi, tumbuh dengan cepat, dan tumor tulang jinak destruktif yang jarang melibatkan tulang-tulang tangan. Patogenesis tumor ini masih kontroversial dan mungkin bersifat kelainan vaskular, traumatis, atau genetik. Penelitian ini bertujuan untuk mengevaluasi pasien setelah injeksi steroid. Seorang anak laki-laki dengan riwayat nyeri dan pembengkakan lokal pada metacarpal kelima tangan kanannya selama dua bulan dengan kondisi hemofilia. Pemeriksaan fisik dan radiografi tangan menegakkan adanya kista tulang aneurisma. Pasien diberi faktor VIII 2 jam sebelum injeksi steroid pada benjolan di atas metacarpal kelima tangan kanannya. Evaluasi sebulan setelah injeksi untuk pasien ini, kami memiliki hasil yang baik secara klinis dan radiologis. Evaluasi radiologis diperoleh penampilan penebalan korteks pada tulang yang terkena. Kami menyimpulkan bahwa injeksi steroid harus dipertimbangkan sebagai salah satu pengobatan kista tulang aneurisma dengan hemofilia, namun hasilnya masih perlu evaluasi lebih lanjut.Kata kunci: Kista Tulang Aneurisma, Hemofilia, Injeksi steroid